PENGARUH VAKSIN HEAT KILLED Salmonella Typhimurium TERHADAP KADAR TUMOR NECROSIS FACTOR ALPHA (TNF-Î±) SERUM PADA TIKUS WISTAR JANTAN YANG DIBERI DIET TINGGI LEMAK - Winarsih, Sri; Santoso, Putu Adi; Derisna, Anak Agung (University of Brawijaya, 2017)
Salmonella Typhimurium that synthesize phosphorylcholine (PC) was able to induce anti-PC antibody responses that cross-react with the PC on oxidized lipoprotein (Ox-LDL).The purpose of this study was to determine the effect of heat killed bacteria vaccine Salmonella Typhimurium in lowering levels of serum TNF-Î± in rat fed by high fat diet. This study was an experimental research laboratory. The vaccine was made by heating 108 S. Typhimurium bacteria at temperature of 100Â°C for 45 minutes on the waterbath. Twenty five male Wistar rats as experimental animals, divided into the negative control group (normal diet) and four treatment groups high fat diet consisting of the positive control group (without vaccination), group A (vaccine 100 Î¼l plus CFA-IFA adjuvant 100 Î¼L), group B (vaccine 100 Î¼L), and group C (CFA-IFA adjuvant 100 Î¼L). The vaccine was injected five times every two weeks, where the vaccine consist of primary injection and four booster injection. The results showed that administration of heat killed S. Typhimurium vaccine plus CFA-IFA can lower the amount of serum levels of TNF-Î± significantly to the positive control group (p < 0,05). The conclusion is the research proved that heat killed Salmonella Typhimurium vaccine with CFA-IFA adjuvant decreases TNF-Î± serum which are proinflammantory cytokine. TNF-Î± is proinflammantory cytokine which has a role in the progression of metabolic syndrome. Further researches about the potential of heat killed S. Typhimurium towards the prevention of the progression of metabolc syndrome are needed to be conducted.Â Keywords: vaccine, Salmonella Typhimurium, TNF-Î±